2022
DOI: 10.3390/jfb13040163
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Microbiological Effect of Colloidal Nanosilver Solution for Root Canal Treatment

Abstract: Background: The goal of endodontic treatment, along with the preparation of the root canal and giving it a shape corresponding to the obturation technique, is the drug treatment of the canal. The aim of this study was to determine the antibacterial effect of a colloidal solution of nanosilver at its various dilutions on root canal microorganism. Materials and methods: A solution of silver nanoparticles at a concentration of 10,000 ppm (1.0%) was diluted in various concentrations (10 solutions from 1% to 0.0025… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
2
2
0
Order By: Relevance
“…S. aureus produces infections, such as bacteremia, endocarditis, pneumonia, and sepsis. Similar inhibitory halos were obtained with both kinds of nanoparticles (Figure 6), suggesting a general way of action of this material, considering the cell wall differences presented between Gram-positive and -negative bacteria [13,51]. On the other hand, regarding the fungicide effect of Fe3O4 particles in eukaryotic cells, it is important to mention the fact that three Candida species were tested: C. albicans, C. parapsilosis, and C. glabrata, all human-life-threatening pathogens due to the high morbidity and mortality [52,53].…”
Section: Antibacterial and Antifungal Activity Assaysupporting
confidence: 76%
See 2 more Smart Citations
“…S. aureus produces infections, such as bacteremia, endocarditis, pneumonia, and sepsis. Similar inhibitory halos were obtained with both kinds of nanoparticles (Figure 6), suggesting a general way of action of this material, considering the cell wall differences presented between Gram-positive and -negative bacteria [13,51]. On the other hand, regarding the fungicide effect of Fe3O4 particles in eukaryotic cells, it is important to mention the fact that three Candida species were tested: C. albicans, C. parapsilosis, and C. glabrata, all human-life-threatening pathogens due to the high morbidity and mortality [52,53].…”
Section: Antibacterial and Antifungal Activity Assaysupporting
confidence: 76%
“…S. aureus produces infections, such as bacteremia, endocarditis, pneumonia, and sepsis. Similar inhibitory halos were obtained with both kinds of nanoparticles (Figure 6), suggesting a general way of action of this material, considering the cell wall differences presented between Gram-positive and -negative bacteria [13,51]. In this sense, it is important to note that the Bc value is nearly zero in three cases; consequently, a superparamagnetic behavior can be considered.…”
Section: Antibacterial and Antifungal Activity Assaysupporting
confidence: 76%
See 1 more Smart Citation
“…This experiment underscores the low cytotoxicity of IR780@FOM-cRGD towards normal cells, demonstrating its favorable in vitro safety profile. 33 , 34 The hemolysis assay results demonstrated that the hemolysis rate remained below 10% for concentrations of IR780@FOM-cRGD up to 100 μg/mL ( Figure 3B ). This finding indicates that IR780@FOM-cRGD possesses favorable in vivo safety characteristic.…”
Section: Resultsmentioning
confidence: 99%